The Struggle of Opu Daeng Risaju and Luwu’s Muslim Community Response to Collonialism - khoirunnisa; fatiyah; sandria (Islah: Journal of Islamic Literature and History, 2025)
Opu Daeng Risaju was a warrior and one of the pioneers of the Indonesian Islamic Union Party (PSII) in Tanah Luwu. Although Opu Daeng Risaju was a woman, her determination and fighting spirit were immense. Opu Daeng Risaju was determined to realize her dream of eliminating the colonizers in Tanah Luwu, South Sulawesi. Opu Daeng Risaju's struggle through the PSII was well received by the Muslim community in Luwu, as the majority of the population in this region is Muslim, making Islamic-oriented movements more easily accepted by the community. This study will examine the response of the Muslim community to Opu Daeng Risaju's struggle against colonialism in Luwu. This study will focus on three main areas of discussion. First, it will discuss the background of the community in Luwu before 1930. Second, it will discuss the efforts made by Opu Daeng Risaju in fighting colonialism in Luwu from 1930 to 1946. Third, it will examine the response of the Muslim community to Opu Daeng Risaju's struggle. This research employs a socio-political approach, utilizing the concept of struggle based on Louis Thurstone's theory of response. The research method used is historical research, involving the steps of heuristics, verification, interpretation, and historiography.